La movilidad de los inmigrantes emprendedores con iniciativas culturales y creativas en la Comunidad de Madrid - OSORIO GARCÍA-OTEYZA, Miguel; JIMÉNEZ-SOSA, Mirian (Revista Iberoamericana de Estudios de Desarrollo)
Cultural and creative industries have an increasing impact on the economic and social development of the 21st century. The main objective of this article is to bring into debate within the academic community the contribution that the Latin American immigrants make to the economic and social development in Madrid through their cultural and creative initiatives. Specifically, we explore through documentary analysis the social dimension of cultural and creative industries in immigrants’ lives as actors of their own future. Elements such as gastronomy, music or religion have always crossed different borders. However, ICT facilitates new migratory flows, such as the mobility of 7entrepreneurs of art and culture. Cultural and creative industries, besides being a resource for economic mobility, are also a source of identity, create a sense of belonging and facilitate social cohesion.